Usuwanie błony granicznej wewnętrznej. Membranektomia mechaniczna i płynowa - Robaszkiewicz, Jacek; Wójcik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The purpose of this study is presentation of some surgical methods used during the removal of internal limiting membrane of retina, or its complex with epiretinal membrane. At the beginning, the procedure was reserved only for difficult cases so in such conditions we can hardly expect very good results. Removing of epiretinal membranes became more common of late twenty years and macular surgery began to comprise greater percentage of vitreoretinal surgeries. Indications for the type of this procedure were significantly enhanced, as well.